Criminal Law Review of Domestic Violence Based on Law Number 23 of 2004 Concerning Domestic Violence: Tinjauan Hukum Pidana Terhadap Kekerasan Dalam Rumah Tangga Berdasarkan Undang-Undang Nomor 23 Tahun 2004 Tentang PKDRT - Agus Rahman; Lilik Warsito; Surya Kusuma Wardana (CV Edujavare Publishing, 2026)
Domestic violence (KDRT) constitutes a distinctive category of crime in that it unfolds within private spaces yet produces serious consequences for victims, families, and broader society. Law Number 23 of 2004 on the Elimination of Domestic Violence (UU PKDRT) was enacted as a legislative response to the limitations of the Criminal Code (KUHP) in addressing offenses committed within domestic settings. This paper examines how UU PKDRT constructs the criminal qualification of domestic violence, analyzes the penal sanctions it prescribes, and evaluates the extent to which this legal instrument provides meaningful protection to victims. A normative juridical method is employed, drawing on statutory and conceptual approaches. The analysis reveals that UU PKDRT introduces a significant expansion of the KDRT definition beyond mere physical violence to encompass psychological, sexual, and neglect-based harm. Nevertheless, its implementation continues to face considerable obstacles, including social stigma that discourages victim reporting, inconsistent interpretation among law enforcement actors, and the inherent tension between punitive criminal sanctions and the victim's restorative needs. The paper concludes that the effectiveness of UU PKDRT depends heavily on the coherent interplay of consistent law enforcement, sustained victim support, and broader public legal literacy.